2012
DOI: 10.1089/dia.2011.0228
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Using the OmniPod System Compared with Conventional Insulin Pumps in Young Adults with Type 1 Diabetes

Abstract: The OmniPod system was well received by young adults with type 1 diabetes experienced with conventional CSII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…10,11 The present study evaluates glycemic outcomes in a large cohort of patients with type 1 diabetes previously treated with MDI or CSII therapy after initiating Omnipod therapy.…”
mentioning
confidence: 99%
“…10,11 The present study evaluates glycemic outcomes in a large cohort of patients with type 1 diabetes previously treated with MDI or CSII therapy after initiating Omnipod therapy.…”
mentioning
confidence: 99%
“…Continuity, which refers to aspects of interventions that facilitate contact between young adults and the diabetes service, was the most prominent theme across studies, occurring in 13 of the 18 studies reviewed . Continuity within diabetes services or in the context of a study was implemented by ensuring that participants met, or were in contact with, the same diabetes team members at each clinic or by a research visit , or by assigning one care coordinator . Hernandez et al .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported on patient satisfaction with the intervention with only one study using a validated measure . Only one of the four Health Service Delivery intervention studies provided feedback from participants on the intervention , with all of those in the structured transition group reporting a good experience of structured transition, whereas 70% of the control group reported a poor/bad experience of the unstructured transition process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations